Use of information and communication techniques and their impact on access control - Torres Quijije, Ángel; Oviedo Bayas, Byron (Journal of business and entrepreneurial studie, 2020)
The development of this research work seeks to build a mechanical electronic system that optimizes the access of the automotive fleet on the campus of Eng. Manuel Haz Álvarez of the State Technical University of Quevedo, improving safety levels by monitoring the vehicles they make use of the internal parking lots of the institution. In order to determine the technology that updates the access of the UTEQ automotive fleet, a comparative analysis of the possible solutions was carried out finding in the radio frequency authentication technology the alternative to meet the institution’s needs in terms of vehicle access control. Users are provided with an identification card that contains basic information of authorized personnel for entry or exit to the institution of higher education, also contains the access code that must be validated by the receiving unit.